THE EFFECTIVENESS OF AUTHENTIC MATERIALS FOR READING COMPREHENSION ON STUDENTS’ MOTIVATION - Hendi Hidayat (Acitya: Journal of Teaching and Education, 2021)
The research is about to find out the students’ motivation through the authentic materials in experimental class and using textbook in control class, and to find out the significant result of students’ motivation between control and experimental class at the tenth grade of SMA Negeri 1 Sumber. The research method is quantitatif research with quasi experimental research design. The population of the research is all of MIPA students at the tenth grade and the sample are students of X MIPA 7 and X MIPA 8 that consist of 72 students. The techniques of collecting data are questionnaire and observation. Therefore, the research findings showed that students’ response in experimental class has a very good result after the treatment with the mean 86.42 from 69.18 and the Paired Sample T-test score is 0.00 means that there is a significant result after the treatment. However, students’ response in control class is not really showed the good result because it decreased from 69.76 to 68.87 with the Paired Sample T-test 0.429 means that there is no significant result after the treatment. In addition, the hypothesis test using Analysis of Covariances (ANCOVA) was pointed out that the significant was 0.00 means lower than 0.05. It is indicated that Ha is accepted, namely there is a significant result of students’ motivation from the use of authentic materials for reading comprehension.